Illustrator CS5 power session - Concepcion, Rafael (Kelbytraining.com, 2010)
"Illustrator CS5 has gone through some major changes. From Beautiful Strokes, to being able to design in a 3D plane, Adobes flagship Illustration software really needs to be experienced to be believed. NAPP Instructor RC Concepcion takes you through all of the changes that have been made in Illustrator CS5. There is no faster way to get up to speed than a power session"--Resource description page.